1987
DOI: 10.1029/jc092ic13p14417
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the marine biota coincident with the 1982–1983 El Niño in the northeastern Subarctic Pacific Ocean

Abstract: The very strong 1982–1983 El Niño is implicated in extraordinary northern range extensions and shifts in population distributions of many species of marine organisms from Oregon to Alaska during 1983. Some species such as Pacific and jack mackerel maintained large populations in the Pacific Northwest during the summer of 1983, as well as the summer of 1984, a year after physical subsidence of the event. Although salmon catches were large in Alaskan waters, populations off Oregon were severely reduced during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 21 publications
4
70
0
Order By: Relevance
“…While extreme El Niño events rarely occurred in history, they had extraordinary impacts on the global climate (Pearcy and Schoener, 1987;Changnon, 2000;Zhan et al, 2016). Previous studies suggested that the genesis of an extreme El Niño could be attributed to the effects from nonlinear convection (Hoerling et al, 1997;Kang and Kug, 2002), biological feedback (Timmermann and Jin, 2002;Marzeion et al, 2005), tropical instability waves (Vialard et al, 2001), and the feedback form the Indian Ocean (Okumura and Deser, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While extreme El Niño events rarely occurred in history, they had extraordinary impacts on the global climate (Pearcy and Schoener, 1987;Changnon, 2000;Zhan et al, 2016). Previous studies suggested that the genesis of an extreme El Niño could be attributed to the effects from nonlinear convection (Hoerling et al, 1997;Kang and Kug, 2002), biological feedback (Timmermann and Jin, 2002;Marzeion et al, 2005), tropical instability waves (Vialard et al, 2001), and the feedback form the Indian Ocean (Okumura and Deser, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…the North Atlantic Oscillation (NAO), El Niño Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO). Strong relationships have been found among the NAO (Ottersen et al 2001, Parsons & Lear 2001, ENSO (Pearcy & Schoener 1987, Sugimoto et al 2001, PDO (Hollowed et al 2001, Royer et al 2001) and the abundance of various marine organisms. In particular, shifts in plankton abundance in relation to climate indices have been well studied in the northeast Atlantic Ocean (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Pearcy & Schoener 1987, Anderson & Piatt 1999. Much of the biota of the North Pacific and Bering Sea was affected by shifts in climate, including changes in abundance of zooplankton, salmon and groundfish (Hare & Mantua 2000).…”
Section: Introductionmentioning
confidence: 99%